Environmental Presence of Mycobacterium tuberculosis Complex in Aggregation Points at the Wildlife/Livestock Interface. Issue 4 (10th February 2016) - Barasona, J. A.; Vicente, J.; Díez‐Delgado, I.; Aznar, J.; Gortázar, C.; Torres, M. J.
Summary: The members of the Mycobacterium tuberculosis complex (MTC) cause tuberculosis (TB). Infection is transmitted within and between livestock and wildlife populations, thus hampering TB control. Indirect transmission might be facilitated if MTC bacteria persist in the environment long enough to represent a risk of exposure to different species sharing the same habitat. We have, for the first time, addressed the relationship between environmental MTC persistence and the use of water resources in two TB endemic areas in southern Spain with the objective of identifying the presence of environmental MTC and its driving factors at ungulates' water aggregation points. Camera‐trap monitoring and MTC diagnosis (using a new MTC complex‐specific PCR technique) were carried out at watering sites. Overall, 55.8% of the water points tested positive for MTC in mud samples on the shore, while 8.9% of them were positive in the case of water samples. A higher percentage of MTC‐positive samples was found at those waterholes where cachectic animals were identified using camera‐trap monitoring, and at the smallest waterholes. Our results help to understand the role of indirect routes of cross‐species TB transmission and highlight the importance of certain environmental features in maintaining infection in multihost systems. This will help to better target actions and implement control strategies for TB at the wildlife/livestock interface.